Household Air Pollution From Solid Cooking Fuel Combustion and Female Breast Cancer - Liu, Tanxin; Chen, Ru; Zheng, Rongshou; Li, Liming; Wang, Shengfeng (Frontiers in Public Health, 2021)
Background: Women bear a large share of disease burden caused by household air pollution due to their great involvement in domestic activities. Pollutant emissions are believed to vary by exposure patterns such as cooking and space heating. Little is known about the independent effect of solid cooking fuel combustion on breast cancer risk. We aimed to examine the association of indoor coal and wood combustion for cooking with breast cancer risk. Methods: During June 2004- July 2008, participants aged 30-79 from 10 diverse regions across China were enrolled in the China Kadoorie Biobank. Primary cooking fuel use information in up to three residences was self-reported at baseline. Multivariable logistic regression models yielded adjusted odds ratios (ORs) and 95% confidence intervals (CIs). Results: A total of 290,396 female participants aged 30-79 were included in the main analysis. Compared with long-term clean fuel users, the fully adjusted ORs were 2.07 (95%CI: 1.37-3.13) for long-term coal users, 1.12 (95% CI: 0.72-1.76) for long-term wood users, and 0.98 (95% CI: 0.55-1.74) for those who used mixed solid fuels to cook. Those who had switched from solid to clean fuels did not have an excess risk of breast cancer (OR: 0.88, 95%CI 0.71-1.10). Conclusion: Long-term solid fuel combustion for cooking may increase the risk of breast cancer. The strength of association is stronger among coal users than wood users. Targeted interventions are needed to accelerate the access to clean and affordable energy.